Level of adherence to diet and physical activity among menopausal women and influencing factors in Jordan: a descriptive cross-sectional study - Alnjadat, Rafi; Momani, Eshraq Al; Etoom, Mohammad; Hamdan, Falastine; ALrub, Salwa Abu (Frontiers in Public Health, 2024)
Background: Menopause can impact a woman's lifestyle, affecting her quality of life. A woman will undergo menopause for over a Menopause factors influence diet and exercise adherence for 2/3 of their lives, therefore excellent health is vital. Menopausal women can stay healthy with a balanced diet and exercise. Thus, menopausal women's food and exercise habits must be assessed.This study evaluates Jordanian menopausal women's food and exercise habits and identifies the most important elements.Methods: 299 menopausal women were randomly sampled and sent an online self-administered questionnaire in this descriptive cross-sectional study. Menopausal women's food and exercise habits were assessed using a valid and reliable questionnaire. The questionnaire had 14 questions: 12 for diet and 2 for physical activity. For data analysis, descriptive statistics, mean weight, and BMI were determined, and stepwise regression was used.Results: Women had moderate diet and exercise adherence (49.25; SD = 7.17). Most individuals (n = 188, 62.9%) ate refined food items once a month or less and did not exercise regularly (n = 119, 39.8%). Only a few (n = 5, 1.7%) ate refined food daily and exercised 5-6 times a week. Age, having two children, and completing elementary or secondary education were the biggest predictors of adherence, according to the regression analysis. The predictors explained 68% of healthy diet and exercise adherence (R 2 =.068, F [343.54] = 7.123, p =.000).This study found that most middle-aged menopausal women ate and exercised moderately. Healthy eating and exercise were linked to age, having two children, and completing primary or secondary education. Therefore, healthcare interventions including physical exercise and food restriction should target women in this age range and stage.